A co-crystallised cobalt(II) cluster of pyridinedicarboxylic acid (PDC) as a luminescent material for selective sensing of methanol - Olayemi, Victoria T.; Tella, Adedibu C.; Adekola, Folahan A.; Clayton, Hadley S.; Oladipo, Adetola C.; Mehlana, Gift; Ogunlaja, Adeniyi S.; Oluwafemi, Oluwatobi S.; Ogar, Joseph O.; Argent, Stephen P.; Mokaya, Robert (Springer, 2022)
A luminescent Cobalt(II) co-crystal [Co13(PDC)16(H2O)24.7H2O] 1 (where H2PDC = 2,6-pyridinedicarboxylic acid) have been prepared by oven-heating and slow evaporation of solvent. Single crystal X-ray diffraction (SCXRD) analysis revealed that 1 is a mixture of complexes that crystallizes in the triclinic space group P-1 and the geometry around the Co(II) ions is octahedral. The structure is extensively imbued with hydrogen bonding that helps in stabilizing the complex. Thermogravimetric analysis indicates that 1 is thermally stable up to 364 οC. The luminescence properties of 1 revealed a strong emission centered at 437 nm (λex = 345 nm) assigned to ligand to metal charge transfer (LMCT). The luminescence sensing of 1 towards volatile organic molecules were also examined. However, 1 displayed a turn off towards methanol compared to other molecules with high quenching efficiency and low limit of detection (3.5 × 10−4 vol%). The results show excellent selectively and high sensitivity. Powder X-ray diffraction studies revealed that the structural integrity of the complex was maintained after exposure to methanol vapour. Theoretical studies also revealed small binding energy (−413.2 au) and low energy gap (1.19) for 1-CH3OH adduct.